Makna Dzikr dan Nisyan Dalam al-Qur’an: Intregasi Tafsir dengan Ilmu Kognitif Modern - Avant Satria; Rosydina Robia'aqolbi (Es-Syajar:Journal of Islam, Science and Technology Integration, 2025)
This study discusses the meaning of dzikr (remembrance) and nisyan (forgetting) in the Qur'an by relating them to the concept of memory in modern cognitive science. This study shows that the Qur'an not only emphasizes spiritual aspects but also pays attention to the psychological mechanisms and cognitive processes that influence how humans remember and forget various life experiences. This study uses a library research approach by examining classical interpretations, cognitive psychology literature, and other scientific sources to find consistent and complementary relationships between the two. Dzikr is understood as a spiritual activity that aims to strengthen human awareness, focus, and relationship with Allah, while fostering inner peace. From a cognitive perspective, dzikr is similar to the process of strengthening memory through repeated attention, repetition of information, and consistent mental exercises that improve memory sharpness. In contrast, nisyan does not only refer to forgetting in a biological context, but also describes spiritual negligence that causes humans to turn away from the values of truth and divine guidance. The integration of these two concepts confirms that human memory is the result of a combination of cognitive, emotional, and spiritual aspects, as well as an ever-evolving state of consciousness.